PERJANJIAN LISENSI SEBAGAI BENTUK PERLINDUNGAN MEREK - Sarah Selfina Kuahaty (SASI, 2015)
One branch of the study of the philosophy of science is the study of value axiology usefulness of science. Studies are generally intended to enhance human dignity. In the field of legal science in particular the Intellectual Property Rights pragmatic development occurs to break the deadlock laws that are exclusive for instance on the right to the brand with the birth of the license agreement that is expected to penetrate the exclusive restrictions earlier. Article 1 point 13 of Act No. 15 of 2001 on Marks, can be known elements in the Law License Brands include any permission granted by Trademark holders. The permission was given in the form of the agreement. The licensing agreement begins with the submission of the prospective licensee to the licensor as a brand owner. Such a request can be interpreted as an effort to permit application of the prospective licensee to use the trademark. If then reached an agreement in the form of the license contract, such agreement as a strong foundation and lawful for the licensee to produce goods or services using the brand licensor. The license agreement has been made between the licensor and the licensee must be registered. Agreements which have been registered prevail throughout Indonesia, unless agreed otherwise. The setting of this region related to territorial restrictions that allow for the exercise of the right of the registered trademark. In the perspective of axiology, a license agreement is very beneficial for others to use a trademark without breaking the law. In contrast to the brand owner, the license agreement is very beneficial for the legal protection of its brand, and can wreak opinions (income) from the payment of royalties received from licensees, if the license agreement is implemented consistently by the parties, it will bring great benefits to the parties , which in turn can bring justice